Why financial incentives can destroy economically valuable biodiversity in Ethiopia - Franz Gatzweiler; Anke Reichhuber; Lars Hein (University of Bonn, Center for Development Research (ZEF), 2007)
Ethiopian montane rainforests are economically valuable repositories of biodiversity, especially of wild Coffea Arabica populations, and they are vanishing at accelerating rates. Our research results confirm theory which explains biodiversity loss by diverging private and social net benefits from land conversion. Poor farmers basically live from hand-to-mouth and manage resources with very short term planning horizons. In such circumstances they cannot afford to carry the cost burden of conservation from which the broader national and global society benefits. Society, on the other hand, highly values the biodiversity of Ethiopia's montane rainforests, but has not managed to put mechanisms in place which enable to pay for the conservation of these values and conservation policies are in place but are not implemented. While it is economically rational for the farmer to convert forests into agricultural land and thereby improve his income (the financial incentive we refer to here), it is economically irrational for national and global society not to pay for conservation. The core reasons for such divergence is that institutions for conservation and sustainable use are not in place. We identify the most important ones and recommend changes for the Ethiopian case.
Keywords: 330; Biodiversität; Kaffee; Landwirtschaft; Umweltbelastung; Landwirtschaftliche Bodennutzung; Naturschutz; Ökonomischer Anreiz; Äthiopien